Portable chlorpyrifos electrochemical aptamer sensor as well as preparation method and application thereof
By modifying AuNPs/Cu-MOF/MWCNTs nanocomposite materials on screen-printed electrodes, a portable electrochemical aptamer sensor for chlorpyrifos was constructed, solving the signal drift problem of nucleic acid aptamer sensors when the sample matrix changes, and realizing efficient and accurate detection of chlorpyrifos.
Patent Information
- Application Number
- CN202511736971.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-25
- Publication Date
- 2026-02-06
AI Technical Summary
Existing nucleic acid aptamer sensors are prone to signal drift when the sample matrix changes, affecting the accuracy and reliability of chlorpyrifos detection.
Using screen-printed electrodes (SPCE) as a substrate, a portable chlorpyrifos electrochemical aptamer sensor was constructed by modifying a novel AuNPs/Cu-MOF/MWCNTs nanocomposite material. Cu-MOF provides a large specific surface area and biocompatibility, MWCNTs improve conductivity, and AuNPs enhance conductivity and provide aptamer connection sites.
It achieved good specificity, stability and reproducibility for chlorpyrifos, and was successfully applied to rapid and sensitive detection in actual radish samples.
Smart Images

Figure CN121476334A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of electrochemical sensors, in particular to a portable chlorpyrifos electrochemical aptamer sensor and a preparation method and application thereof. BACKGROUND
[0002] A nucleic acid aptamer is a new type of molecular recognition element, which is suitable for developing a sensing interface of an electrochemical biosensor. Metal-organic frameworks (MOFs) are a new type of porous material synthesized by connecting metal-containing nodes to organic bridging ligands. Aptamers have the advantages of small molecular weight, non-toxicity, non-immunogenicity, good tissue permeability and the like, and at present, the aptamers have been widely applied to analytical chemistry, biochemistry, food and other fields.
[0003] However, the function of the aptamer depends on its three-dimensional spatial structure. Changes in factors such as pH value, ionic strength and organic solvent in a sample matrix can cause non-specific changes in the conformation of the aptamer, produce signal drift unrelated to the target chlorpyrifos or false positive / false negative results, and affect the accuracy and reliability of detection. SUMMARY
[0004] To solve the above technical problems, the application aims to provide a portable chlorpyrifos electrochemical aptamer sensor and a preparation method and application thereof. The electrochemical sensor has good specificity, stability and reproducibility for chlorpyrifos, and is successfully applied to detection in a radish actual sample, and has great potential in the field of rapid and sensitive detection of pesticide residues.
[0005] To solve the above problems, the following technical scheme is provided: a portable chlorpyrifos (CPF) electrochemical aptamer sensor, wherein the sensor is constructed by modifying a novel AuNPs / Cu-MOF / MWCNTs nanocomposite material based on a screen-printed electrode (SPCE).
[0006] A preparation method of the portable chlorpyrifos electrochemical aptamer sensor comprises the following steps: (1) Cu-MOF preparation Cu(NO3)2 6H2O and H3BTC are respectively dissolved in deionized water and ethanol, the solutions are mixed in a polytetrafluoroethylene liner, and the liner is placed in a high-pressure kettle; the high-pressure kettle is heated at 150°C for 24 hours, and then slowly cooled to room temperature; after the blue powder is centrifuged, washed with water and washed with DMF, the powder is dried under vacuum at 80°C, and is prepared for use; (2) Preparation of carboxylated MWCNTs MWCNTs were dispersed in a solution of concentrated sulfuric acid and concentrated nitric acid and refluxed at 80 °C for 10 h. The resulting solid was then washed with ultrapure water and freeze-dried when the pH of the washing filtrate was neutral. (3) Preparation of Cu-MOF / MWCNTs composite materials The prepared Cu-MOF and carboxylated MWCNTs were ultrasonically dispersed in a solution containing chitosan, and a uniform Cu-MOF / MWCNTs composite material was obtained after dispersion. (4) Electrode modification The Cu-MOF / MWCNTs composite was subjected to SPCE at 40-60 mV s -1 The scan rate at Electropolymerization was performed for 2-4 cycles within a potential range of 0.3–1.0 V, followed by deposition in 6.0 mM HAuCl4 at different deposition potentials (from...). 0.1~ AuNPs were deposited on SPCE at different times (100–500 s) and at 0.5 V. After electrodeposition, the modified electrode was rinsed with ultrapure water and allowed to air dry. Before use, the electrode was placed in 0.1 M PBS and electrodeposited at 100 mV s in a potential window of 0.8–1.3 V. -1 The scanning rate was maintained until a stable cyclic voltammetric response was obtained, thus forming an AUNPs / Cu-MOF / MWCNTs composite material. (5) Fabrication of aptamer sensors The AUNPs / Cu-MOF / MWCNTs composite material was allowed to air dry at room temperature. 4-6 μL of chlorpyrifos aptamer was dropped onto the electrode surface and allowed to air dry. Then, 5 μL of 0.5% bovine serum albumin solution was dropped onto the electrode surface and allowed to air dry. Next, 5 μL of 0.5% bovine serum albumin solution was dropped onto the electrode surface and allowed to react for 30 minutes. Finally, the chlorpyrifos solution was added to the electrode. After the electrode dried, it was ready for detection.
[0007] Furthermore, 0.25g Cu(NO3)26H2O and 0.25g H3BTC were dissolved in 7.1ml deionized water and 7.1ml ethanol, respectively. The solutions were mixed in a polytetrafluoroethylene liner and placed in an autoclave. The autoclave was heated at 150°C for 24 hours and then slowly cooled to room temperature. The blue powder was centrifuged (14000rpm, 5 min), washed with water and DMF, and then dried under vacuum at 80°C for 24 hours for later use.
[0008] Furthermore, in step (2), the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1.
[0009] Further, 2mg of the prepared Cu-MOF and 400ul of 5mg / ml carboxylated MWCNTs were ultrasonically dispersed in a chitosan solution containing 2ml, and dispersed for 15min to obtain a uniform Cu-MOF / MWCNTs composite material.
[0010] Further, the nucleic acid sequence of the chlorpyrifos aptamer is 5'-CCTGCCA CGCTCCGCAAGCTTAGGGTTACGCCTGCAGCGATTCTTGATCGCGCTGCTGGTAATCCTTCTT TAAGCTGGCACCCGCATCGT-3'.
[0011] Application of the portable chlorpyrifos electrochemical aptamer sensor in chlorpyrifos detection.
[0012] Application of the portable chlorpyrifos electrochemical aptamer sensor in pesticide residue detection.
[0013] Beneficial effects The sensor prepared by the application uses a nucleic acid aptamer as a molecular recognition element. Compared with traditional antibodies, the aptamer has the advantages of small molecular weight, non-toxicity, non-immunogenicity, good tissue permeability, and the like, which provides an ideal sensing interface for the development of electrochemical biosensors. By replacing different aptamers, the detection of other pesticide residues of radish can be realized.
[0014] The construction of the nanocomposite material fully utilizes the advantages of each component: Cu-MOF provides a large specific surface area and good biocompatibility; MWCNTs have high electrical conductivity, which improves the defect of poor electrical conductivity of Cu-MOF; and AuNPs are used to enhance the electrical conductivity, amplify the electrical signal, and provide a site for connecting the aptamer.
[0015] The sensor modification process adopts a combination technique: firstly, the Cu-MOF / MWCNTs composite material is stably modified on the surface of the SPCE through electro-polymerization, and then AuNPs are attached through electro-deposition technology. This combination method improves the electrical conductivity and the attachment rate of gold ions, which helps to improve the detection limit of the sensor. Finally, the specific aptamer of chlorpyrifos is fixed on the electrode surface by forming a gold-sulfur bond between AuNPs and the specific aptamer of chlorpyrifos.
[0016] The experimental results show that the electrochemical sensor has good specificity, stability and reproducibility for chlorpyrifos, and is successfully applied to the detection of radish actual samples, and has great potential in the field of rapid and sensitive detection of pesticide residues. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 The figure shows a schematic diagram of the sensor assembly process; Figure 2The material morphology transmission spectrum of Cu-MOF is shown; Figure 3 The scanning electron microscope image of Cu-MOF / MWCNTs is shown; Figure 4 The EDS characterization graph of AuNPs / Cu-MOF / MWCNTs is shown; Figure 5 The cyclic voltammograms (CV) of the modified electrode at each step in the modification process are shown; Figure 6 The impedance graph (CV) of the modified electrode at each step in the modification process is shown; Figure 7 The relationship between different pH values and current intensity is shown; Figure 8 The relationship between different concentrations of aptamers and current intensity is shown; Figure 9 The effect of incubation time on current intensity is shown; Figure 10 The stability test graph of the sensor is shown; Figure 11 The repeatability test graph of the sensor is shown; Figure 12 The specificity result graph of the sensor is shown; Figure 13 The cyclic voltammograms of the electrochemical sensor detecting different concentrations of chlorpyrifos (0.1-105 ng / ml) are shown; Figure 14 The relationship between chlorpyrifos concentration and current intensity is shown. DETAILED DESCRIPTION In order to make the person skilled in the art better understand the technical solutions in the present application, the present application will be further described below in combination with examples, and the described examples are only some of the examples of the present application, not all, and the present application is not limited by the following examples. The implementation conditions used in the examples can be further adjusted according to the specific conditions of the manufacturer, and the implementation conditions not specified are usually the conditions in the conventional experiments.
[0018] 1. A preparation method of a portable chlorpyrifos electrochemical aptamer sensor, comprising the following steps: (1) Preparation of Cu-MOF First, 0.25 g of Cu(NO3)2 6H2O and 0.25 g of H3BTC were dissolved in 7.1 ml of deionized water and 7.1 ml of ethanol, respectively. The solution was mixed in a polytetrafluoroethylene liner and placed in an autoclave. The autoclave was heated at 150°C for 24 hours, and then slowly cooled to room temperature. The blue powder was centrifuged, washed with water and DMF, and then dried at 80°C under vacuum for 24 hours for standby use.
[0019] (2) Preparation of carboxylated MWCNTs MWCNTs were dispersed in a solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1) and refluxed at 80 °C for 10 h. The resulting solid was then washed with ultrapure water and freeze-dried when the pH of the washing filtrate was neutral.
[0020] (3) Preparation of Cu-MOF / MWCNTs composite materials 2 mg of the prepared Cu-MOF and 400 μl of 5 mg / ml carboxylated MWCNTs were ultrasonically dispersed in a chitosan solution containing 2 ml and dispersed for 15 min to obtain a uniform Cu-MOF / MWCNTs composite material.
[0021] (4) Electrode modification The Cu-MOF / MWCNTs composite was subjected to 50 mV s on SPCE. -1 The scan rate at Electropolymerization was performed twice within a potential range of 0.3–1.0 V, followed by polymerization in 6.0 mM HAuCl4. AuNPs 200s were deposited on SPCE at a deposition potential of 0.2 V. After electrodeposition, the modified electrode was rinsed with ultrapure water and allowed to air dry. Before use, the electrode was placed in 0.1 M PBS and electrodeposited at 100 mV s in a potential window of 0.8–1.3 V. -1 The scanning rate was maintained until a stable cyclic voltammetric response was obtained, thus forming an AUNPs / Cu-MOF / MWCNTs composite material.
[0022] (5) Fabrication of aptamer sensors The AUNPs / Cu-MOF / MWCNTs composite material was allowed to air dry at room temperature. 5 μL of chlorpyrifos aptamer (5'-CCTGCCA CGCTCCGCAAGCTTAGGGTTACGCCTGCAGC GATTCTTGATCGCGCTGCTGGTAATCCTTCTTTAAGCTGGCACCCGCATCGT-3') was dropped onto the electrode surface and allowed to air dry, immobilizing the aptamer on the electrode surface through gold-sulfur bonds formed between the aptamer and the AuNPs. Then, 5 μL of 0.5% bovine serum albumin (BSA) solution was dropped onto the electrode surface to block non-specific binding sites, and the reaction was allowed to proceed for 30 minutes to further block these sites. Finally, chlorpyrifos solution was added to the electrode; the aptamer bound to the material captured antibiotic molecules, causing a change in conductivity. When the electrode was dry, the concentrations of chlorpyrifos solution were monitored by detecting the potential difference after blocking (after BSA addition) and after the addition of chlorpyrifos. Figure 1A schematic of the sensor assembly process is described.
[0023] 2 Actual sample detection: Radish samples were purchased from a local supermarket (Jinan, China) and selected for CPF analysis. The edible part of radish was taken, and after sub-division, chopped and mixed, put into a homogenizer for crushing. 0.5 g of sample was weighed, 25 ml of acetonitrile was added, and ultrasonic extraction was performed for 15 minutes. After filtration, the filtrate to be tested was obtained. The chlorpyrifos standard solution was added to the test solution to prepare samples of different concentrations (1 ng mL-1, 100 ng mL-1, 10000 ng mL-1) for analysis and determination.
[0024] 3. Results and analysis (1) TEM characterization of Cu-MOF As shown in the transmission spectrum, it can be seen from the characterization results that the particle distribution of Cu-MOF is relatively uniform, and the particle size is between 100-200 nm, and its crystal is a three-dimensional structure. Figure 2 (2) SEM characterization of Cu-MOF / MWCNTs
[0025] As shown in the transmission spectrum, it can be seen from the characterization results that the particle distribution of Cu-MOF is relatively uniform, and the particle size is between 100-200 nm, and its crystal is a three-dimensional structure. As shown in the transmission spectrum, it can be seen from the characterization results that the particle distribution of Cu-MOF is relatively uniform, and the particle size is between 100-200 nm, and its crystal is a three-dimensional structure. Figure 3 As shown in the transmission spectrum, it can be seen from the characterization results that the particle distribution of Cu-MOF is relatively uniform, and the particle size is between 100-200 nm, and its crystal is a three-dimensional structure.
[0026] (3) EDS characterization of AuNPs / Cu-MOF / MWCNTs: From the EDS image, it can be seen that the composite contains C, Cu, Au and O elements, which further proves that the AuNPs / Cu-MOF / MWCNTs composite is successfully synthesized, and MWCNTs occupies a dominant position. Figure 4 (4) Electrochemical characterization of Apt / AuNPs / Cu-MOF / MWCNTs electrochemical sensor
[0027] In order to verify the structure of the electrochemical sensor, the cyclic voltammograms (CV) of the modified electrode in each step of the modification process were obtained. As shown in In order to verify the structure of the electrochemical sensor, the cyclic voltammograms (CV) of the modified electrode in each step of the modification process were obtained. As shown in Figure 5As shown, the experimental temperature was set to room temperature, and the aptamer concentration was set to 5 μΜ. The CV of the unmodified screen-printed electrode showed a pair of obvious redox peaks, indicating that the electrode had good performance. After the surface of the SPCE was modified with the AuNPs / Cu-MOF / MWCNTs composite material, the peak current of the CV increased significantly, indicating that the composite material could achieve good electron transfer. When the cpf aptamer was assembled on the electrode surface, it hindered the charge transfer between the liquid and the electrode, resulting in a decrease in the peak current. The active area of the assembled electrode was further reduced after the electrode surface was covered with BSA. As we expected, the addition of cpf caused the peak current to decrease again because the specific binding of the cpf aptamer and cpf hindered electron transport. The impedance diagram was consistent with the results of the cyclic voltammogram. The smaller the peak current, the greater the impedance, and the greater the peak current, the smaller the impedance, as shown in Figure 6 .
[0028] (5) Optimization of experimental parameters pH As shown in Figure 7 , the overall trend of the current intensity was rising before ph to 7, the current intensity reached the maximum at ph = 7, and the current intensity decreased with the increase of ph after ph = 7. The results showed that an excessively acidic or alkaline environment could affect the response of the electrochemical sensor by affecting the activity of the aptamer and the stability of the composite material. ph = 7 was the best ph for the experiment.
[0029] (6) Optimization of experimental parameters aptamer concentration The effect of aptamer concentration on current intensity was then discussed, as shown in Figure 8 , the current intensity gradually increased from 2 µM to 5 µM of aptamer concentration. The current intensity reached a maximum at 5 µM of aptamer concentration, and then gradually decreased with the increase of aptamer concentration. The reason may be that a high concentration of aptamer can form a stack and entanglement phenomenon on the electrode surface, which is not conducive to the conductivity of the sensor. Therefore, 5 μΜ was used for subsequent experiments.
[0030] (7) Optimization of experimental parameters incubation time The effect of incubation time on the intensity of the aptamer sensor was investigated Figure 9 . With the extension of incubation time, the current intensity reached a maximum at 40 min, and then gradually decreased. The reason may be that the activity of the aptamer is affected with the increase of incubation time, and the blocking effect of BSA cannot be achieved with too low incubation time, which can lead to a decrease in current intensity. Therefore, an incubation time of 40 min was chosen for subsequent experiments.
[0031] (8) Stability, reproducibility, and specificity of the sensor Figure 10is a stability test chart, 20 electrodes are prepared under the same conditions, and every 4 electrodes are a parallel, and the current intensity is detected. As shown in the figure, the current intensity of the electrode after 14 days is 94.7% of that after 7 days, the current intensity after 21 days is 91.2% of that after 7 days, the current intensity after 28 days is 85.4% of that after 7 days, and the current intensity after 35 days is 85.1% of that after 7 days. The results show that as the storage time increases, the electrochemical performance of the sensor is affected to a certain extent, and the electrochemical performance becomes about 85% of the original after one month.
[0032] Figure 11 is a repeatability test chart, 4 electrodes are prepared under the same conditions, and each electrode is added in the order of modification material, aptamer, BSA and antibiotic, and the current intensity is detected. The results show that the relative standard deviation of the four electrodes is 2.47%, indicating that the aptamer sensor has good reproducibility.
[0033] We selected 5 pesticides (omethoate, malathion, dichlorvos, glyphosate, and temephos) to test their specificity, and the results are shown in Figure 12 . It was found that at the same concentration, neither single system nor mixed system could effectively inhibit the current intensity when the system contained 5 undetected pesticides. When the system contained detected pesticides, the current intensity increased significantly. The results show that the electrochemical sensor has good specificity for CPF and can be used for actual detection.
[0034] (9) Analysis of aptamer sensor Under the optimal detection conditions, the prepared aptamer sensor was used to detect chlorpyrifos. Figure 13 and 14 show the relationship between chlorpyrifos concentration and current intensity. With the increase of chlorpyrifos concentration, the current intensity gradually increases. Within a certain concentration range, R 2 =0.998, the current intensity has a good linear relationship with the logarithm of the chlorpyrifos concentration. As shown in Figure 10, with the increase of chlorpyrifos concentration, the number of chlorpyrifos molecules captured by the aptamer increases, resulting in an increase in the blocking effect of the current on the electrode surface, and the current difference becomes larger, i.e. linearly increases within a certain range.
[0035] (10) Detection of actual samples First, as a reference detection, liquid chromatography-tandem mass spectrometry (LC-MS / MS) has confirmed that there is no chlorpyrifos residue. After centrifugation, the sample was filtered through a sterile microporous membrane, diluted 5 times with PBS solution (pH=7.5) for analysis and determination, and each concentration was repeated 3 times. As shown in the table, the recovery rate obtained is from to, and the relative standard deviation (RSD) is between and. According to these results, the proposed aptamer sensor has great potential for sensitive determination of terramycin in actual samples.
[0036]
[0037] 4. Conclusion In this work, a novel electrochemical aptamer sensor was designed for oxytetracycline detection. In this process, AuNPs / Cu-MOF / MWCNTs composite material was synthesized. Cu-MOF has a large specific surface area and good biocompatibility, which can be used as a material to load biological recognition and increase the specific surface area of the electrochemical reaction interface. MWCNTs has high conductivity but low specific capacitance. AuNPs can interact strongly with biological materials and are used as a medium to fix aptamers and enhance current response when constructing a sensitive current-type sensor. The above materials can be compounded to take advantage of their respective advantages and make up for each other's defects. It is hoped that this work will provide ideas for subsequent electrochemical methods for detecting oxytetracycline.
Claims
1. A portable chlorpyrifos electrochemical aptamer sensor, characterized in that: The sensor is constructed using a screen-printed electrode as a substrate and modified with a novel AuNPs / Cu-MOF / MWCNTs nanocomposite material.
2. The method for preparing a portable chlorpyrifos electrochemical aptamer sensor according to claim 1, characterized in that, It includes the following steps: (1) Preparation of Cu-MOF Cu(NO3)2 6H2O and H3BTC were dissolved in deionized water and ethanol, respectively. The solutions were mixed in a polytetrafluoroethylene liner and placed in an autoclave. The autoclave was heated at 150°C for 24 hours and then slowly cooled to room temperature. The blue powder was centrifuged, washed with water and DMF, and then dried under vacuum at 80°C for later use. (2) Preparation of carboxylated MWCNTs MWCNTs were dispersed in a solution of concentrated sulfuric acid and concentrated nitric acid and refluxed at 80 °C for 10 h. The resulting solid was then washed with ultrapure water and freeze-dried when the pH of the washing filtrate was neutral. (3) Preparation of Cu-MOF / MWCNTs composite materials The prepared Cu-MOF and carboxylated MWCNTs were ultrasonically dispersed in a solution containing chitosan, and a uniform Cu-MOF / MWCNTs composite material was obtained after dispersion. (4) Electrode modification The Cu-MOF / MWCNTs composite was subjected to SPCE at 40-60 mV s -1 The scan rate at Electropolymerization was performed for 2-4 cycles within a potential range of 0.3–1.0 V, followed by deposition in 6.0 mM HAuCl4 at different deposition potentials. 0.1~ AuNPs were deposited on SPCE at 0.5 V and different deposition times (100–500 s). After electrodeposition, the modified electrode was rinsed with ultrapure water and allowed to air dry. Before use, the electrode was placed in 0.1 M PBS and depositioned at 100 mV / s within a potential window of 0.8–1.3 V. -1 The scanning rate was maintained until a stable cyclic voltammetric response was obtained, thus forming an AUNPs / Cu-MOF / MWCNTs composite material. (5) Fabrication of aptamer sensors The AUNPs / Cu-MOF / MWCNTs composite material was allowed to air dry at room temperature. 4-6 μL of chlorpyrifos aptamer was dropped onto the electrode surface and allowed to air dry. Then, 5 μL of 0.5% bovine serum albumin solution was dropped onto the electrode surface and allowed to react for 30 minutes. Finally, the chlorpyrifos solution was added to the electrode. Once the electrode was dry, it was ready for detection.
3. The method for preparing a portable chlorpyrifos electrochemical aptamer sensor according to claim 2, characterized in that, 0.25g Cu(NO3)2 6H2O and 0.25g H3BTC were dissolved in 7.1ml deionized water and 7.1ml ethanol, respectively. The solutions were mixed in a polytetrafluoroethylene liner and placed in an autoclave. The autoclave was heated at 150°C for 24 hours and then slowly cooled to room temperature. The blue powder was centrifuged at 14000rpm for 5 min, washed with water and DMF, and then dried under vacuum at 80°C for 24 hours for later use.
4. The method for preparing a portable chlorpyrifos electrochemical aptamer sensor according to claim 2, characterized in that, In step (2), the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:
1.
5. The method for preparing a portable chlorpyrifos electrochemical aptamer sensor according to claim 2, characterized in that, The 2 mg Cu-MOF and 400 μl of 5 mg / ml carboxylated MWCNTs prepared in the first step were ultrasonically dispersed in a chitosan solution containing 2 ml and dispersed for 15 min to obtain a uniform Cu-MOF / MWCNTs composite material.
6. The method for preparing a portable chlorpyrifos electrochemical aptamer sensor according to claim 2, characterized in that, The nucleic acid sequence of the chlorpyrifos aptamer is as follows: 5'-CCTGCCA CGCTCCGCAAGCTTAGGGTTACGCCTGCAGCGATTCTTGATCGCGCTGCTGGTAATCCTTCTT TAAGCTGGCACCCGCATCGT-3'.
7. The application of the portable chlorpyrifos electrochemical aptamer sensor prepared by the method described in claims 2-6 in the detection of chlorpyrifos.
8. The application of the portable chlorpyrifos electrochemical aptamer sensor prepared by the method described in claims 2-6 in pesticide residue detection.
Citation Information
Patent Citations
Preparation method of aptamer sensor for detecting chlorpyrifos
CN105301077A
Electrochemical sensor for adapters and method for detecting chlorpyrifos
CN107367540A
Double-amplification electrochemiluminescence sensor and method for determining chlorpyrifos
CN113970580A
Preparation method of ratio type electrochemical aptamer sensor based on Cu-MOF
CN116429855A
AuNPs (at) Cu-MOF / MWCNTs surface modification electrochemical sensor and preparation method and application thereof
CN117347445A